In vitro cytotoxic activity of rhizome extracts of Cyperus rotundus (L.) against colon carcinoma and Ehrlich ascites carcinoma - Hema Nidugala, Ramakrishna Avadhani, Ashwini Prabhu, Ravishankar Basavaiah (Journal of Applied Pharmaceutical Science, 2016)
Cyperus rotundus (L.) is a perennial herb belonging to family Cyperaceae having tremendous medicinal properties and it has been used in various formulations of Indian system of medicine. This study was designed to investigate the in vitro anticancer potential of aqueous and ethanol extracts of Cyperus rotundus (L.).The cytotoxicity was assessed using SRB Assay and Trypan blue assay against human colon cancer cell line (HCT-116) and Ehrlich Ascites Carcinoma (EAC) cell lines. Results of SRB assay on HCT-116 cells indicated an IC50 value of 517.828 µg/ml for aqueous extract and that 72.06 µg/ml for ethanol extract. In trypan blue assay, IC50 values of 2158.63 µg/ml and 160.19 µg/ml were obtained for aqueous and ethanol extracts respectively on EAC cells. Positive control Doxorubicin exhibited IC50 of 11.221 µg/ml and 23.325 µg/ml against HCT-116 and EAC cells respectively. Findings from this study prospect the possible use of C. rotundus as a potential source of anticancer agent.
Keywords: Cyperus rotundus, Anticancer activity, SRB Assay, Trypan Blue assay, EAC, Colon cancer.